The Structure of Healthy Life Determinants Lessons from the Japanese Aging Cohort Studies (International Perspectives on Aging,, 2018)
This book is the first one to examine the cause and effect of elderly people's healthy life expectancy, providing models that are easy to understand. The novel point is the success achieved in constructing a single structural model of cause and effect of healthy life expectancy. In the final models of the authors' studies, it was possible to clearly point out that it is not the case that lifestyle habits including an ideal diet directly provide for healthy life expectancy. This book is made up of published studies based on scientific evidence, using a vast amount of data based on about 8,000 in-home elderly people tracked longitudinally from 3 to 6 years, three times in all including baseline research, in a specific region of Japan. Therefore, health policy makers will be able to use this book as scientific evidence for creating area programs to promote good health that are focused on healthy longevity as the central issue. Academic researchers whose special fields are mainly public health will be able to learn both theory and practice to structurally analyze cause and effect of health factors.